Short-hairpin RNA-mediated stable silencing of Grb2 impairs cell growth and DNA Synthesis - Di Fulvio, Mauricio (2007)
Grb2 is an SH2-SH3 protein adaptor responsible for linking growth factor receptors with intracellular signaling cascades. To study the role of Grb2 in cell growth, we have generated a new COS7 cell line (COS7(shGrb2)), based on RNAi technology, as null mutations in mammalian Grb2 genes are lethal in early development. This novel cell line continuously expresses a short hairpin RNA that targets endogenous Grb2. Stable COS7(shGrb2) cells had the shGrb2 integrated into the genomic DNA and carried on <10% of normal levels of Grb2. Silencing Grb2 expression reduced, but did not eliminate, basal cell growth rate. This could be reversed, by either the addition of neomycin to the cell cultures or by rescuing with an Xpress-Grb2(SiL) construct (made refractory to the shRNA-mediated interference), but not with an SH2-deficient mutant (R86K). Thus, a viable knock-down and rescue protocol has demonstrated that Grb2 is crucial for cell proliferation.